2020
DOI: 10.31067/0.2020.295
|View full text |Cite
|
Sign up to set email alerts
|

Hemşirelerin İletişim Becerileri ve Öfke Yönetimlerinin Belirlenmesi

Abstract: Amaç: Hemşirelerin iletişim becerileri ve öfke yönetimleri arasındaki ilişkinin belirlenmesi amaçlanmıştır. Gereç ve Yöntem: Bu çalışma, tanımlayıcı bir araştırmadır. Çalışma, Ankara/Türkiye'de bir eğitim ve araştırma hastanesinde Mart-Haziran 2017 tarihleri arasında 144 hemşire ile yapılmıştır. Çalışmanın verileri, sosyo-demografik veri toplama formu, İletişim Becerileri Envanteri (İBE) ve Sürekli Öfke ve Öfke İfade Tarzı Ölçeği (SÖÖTÖ) kullanılarak toplanmıştır. Verilerin analizi, SPSS 22.0 paket programında… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In the study, it was seen that communication skills of the nurses were above the moderate. In the study by Aydogan and Ozkan (2020), mean CSI total and subscale scores were found to be at a moderate level. Similarly, communication skills of the nurses were reported to be above the moderate or high also in many other studies (Caliskan & Ozkan, 2020;Karaman et al, 2016).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In the study, it was seen that communication skills of the nurses were above the moderate. In the study by Aydogan and Ozkan (2020), mean CSI total and subscale scores were found to be at a moderate level. Similarly, communication skills of the nurses were reported to be above the moderate or high also in many other studies (Caliskan & Ozkan, 2020;Karaman et al, 2016).…”
Section: Discussionmentioning
confidence: 83%
“…Personal Information Form: It was composed of a total of 11 questions including sociodemographic characteristics of the nurses (age, sex, marital status, education level, number of children) and professional characteristics (working style, professional experience, working unit, position, willingness to choose profession and status of considering communication education during in-service training as sufficient) (Aydogan & Ozkan, 2020;Erci et al, 2017;Karadag et al, 2015).…”
Section: Study Setting and Samplementioning
confidence: 99%